Lao People's Democratic Republic : Poverty Reduction Strategy Paper Preparation Status Report. (IMF Staff Country Reports; Country Report ;, 2003)
This Status Report summarizes the main steps that have been undertaken since the last progress report to finalize the National Poverty Eradication Program (NPEP) of Lao People's Democratic Republic. The NPEP is a comprehensive framework for growth and development, with a focus of an in-depth improvement of the poverty situation in the poorest districts. It is the government's operational planning instrument, based on active participation at all levels, to achieve growth and poverty eradication. The NPEP monitoring will be completed by a separate monitoring of the progress achieved toward the MDGs.